Neurofeedback in attention-deficit/hyperactivity disorder – different models, different ways of application - Gevensleben, Holger; Moll, Gunther H.; Rothenberger, Aribert; Heinrich, Hartmut (Frontiers in Human Neuroscience, 2014)
In children with ADHD, different neurofeedback (NF) protocols have been applied, with the most prominent differentiation between EEG frequency-band (e.g. theta / beta) training and training of slow cortical potentials (SCPs). However, beyond distinctions between such basic NF variables, there are also competing assumptions about mechanisms of action (e.g., acquisition of regulation capability, generalization to daily life behavior). In the present article, we provide a framework for NF models and suppose two hypothetical models, which we call "conditioning-and-repairing" model and "skill-acquisition model", reflecting extreme poles within this framework. We argue that the underlying model has an impact not only on how NF is applied but also on the selection of evaluation strategies and suggest using evaluation strategies beyond beaten paths of pharmacological research. Reflecting available studies, we address to what extent different views are supported by empirical data. We hypothesize that different models may hold true depending on the processes and behaviors to be addressed by a certain NF protocol. For example, the skill-acquisition model is supported by recent findings as an adequate explanatory framework for the mechanisms of action of SCP training in ADHD. In conclusion, evaluation and interpretation of NF trials in ADHD should be based on the underlying model and the way training is applied, which, in turn, should be stated explicitly in study reports.